Time-Resolved Exploration of a photoCORM Ru(bpy) - Levin, Natalia; Marcolongo, Juan Pablo; Cadranel, Alejandro; Slep, Leonardo Daniel (Inorganic Chemistry)
The carbon monoxide (CO)-photoreleasing molecule [Ru(Me3[9]aneN3)(bpy)(CO)]2+ (RuCO2+ bpy = 2,2′-bipyridine) was prepared and structurally characterized. The photochemical behavior was studied in unprecedented detail for this type of system, using a combination of steady-state and ultrafast transient absorption experiments, which unveiled that 3MLCT and 3dd excited states participate in the decay cascade of photoexcited RuCO2+. Theoretical calculations yield a consistent picture, providing details of the electronic structure of the transient species involved. Our results suggest that the photorelease of CO involves excited states of different electronic nature that are populated sequentially and in parallel. This complex scenario strengthens the idea that the rational design of a good photoCORM is a difficult task to carry out solely using the tools provided by chemical intuition: it is necessary to control by design factors that favor the population of specific photoactive electronic states with respect to those that are not.
CRIS-Team Scopus Importer:2020-09-18